ANALISIS PENDAPATAN USAHATANI CABAI MERAH (Capsicum annum L.) (Studi kasus di Dusun Teguhan Desa Mendogo Kecamatan Ngimbang). - Hamidah, Emmy (saintis, 2016)
Chili is the leading commodities that have economic value, so much cultivated in Indonesia because of its market demand is quite large. Red chili is widely used as a raw material for the processing industry (food, drugs and cosmetics). This research aims to know the red chili pepper cultivation, ranging from nursery to care, fertilization, harvesting. In addition to analyzing the magnitude of the rate of profit can be obtained. The place is the village Teguhan Research Sub Ngimbang Lamongan. Site selection is purposive. In this research I use the sample methods, namely, interviewing some of the farmers who represent entirely.Income is the retribution of the factors of production farmer. The two principal information needed in the analysis of the income of the farmer in order to have practical meaning. The advantage gained from a farmer can be seen from the receipts and expenditure in a certain time limit. The village of chili farming is still profitable, this is indicated by the value of R/C Ratio of 6.05.